Analisis Hubungan Dinas Publik Antara Pegawai Pemerintah Dengan Perjanjian Kerja Dan Pemerintah - Nurmalita Ayuningtyas Harahap (Widya Yuridika, 2021)
In Article 1 point 4 of Law no. 5 of 2014 states that, "Government Employees with Work Agreements, hereinafter abbreviated as PPPK, are Indonesian citizens who meet certain requirements, who are appointed based on work agreements for a certain period of time in order to carry out government duties." One of the characteristics of civil servants who work in government agencies is to have a relationship between civil servants and the government. This relationship is known as opebare dienstbetrekking or Public Service Relations. A voluntary agreement or a special contract due to the appointment that gives rise to the HDP is a one-sided legal act (aanstelling) from the Government. This one-sided government action was marked by the issuance of a Decree of appointment given to Civil Servants. Meanwhile, PPPK is appointed based on a work agreement. Appointments with this work agreement will be understood by their appointments based on ordinary contracts or two-sided government actions. The purpose of this study is to find out the appointment of PPPK is normatively reviewed and analyzes related to PPPK which can be classified or not as Civil Servants who have the characteristics of Public Service Relations with the Government due to the appointment of PPPK based on a work agreement. This type of research is a normative juridical research based on primary and secondary legal materials. The study was carried out using a conceptual approach and a statutory approach. This research is a library research.